Health Belief Model Correlates of Behavioural Response to Diabetic Retinopathy Warning Signs Among Older Adults with Type 2 Diabetes: A Cross-Sectional Study in Rural Northeast Thailand - Weerasak Aneksak; Doonnaput Khowhit; Nakkharot Daengwongsa; Aranya Chaithawatwibun; Natthawut Suriya (National Journal of Community Medicine, 2026)
Background: Diabetic retinopathy (DR) is an avoidable cause of sight loss among adults whose type 2 diabetes mellitus (T2DM) is poorly controlled. Despite Thailand’s subsidised retinal-screening programme, uptake among rural older adults remains suboptimal. The objectives were to describe DR warning-sign awareness (WSAS) and Health Belief Model (HBM) construct scores, and to identify independent correlates of behavioural response to DR warning signs (WSBRS) after adjustment for sociodemographic covariates. Methods: This cross-sectional study enrolled 218 older adults (aged ≥60 years; HbA1c ≥7.0%) attending sub-district diabetes clinics in Mahasarakham Province, Thailand. Structured interviews assessed six HBM constructs, WSAS, and WSBRS on validated five-point Likert scales (Cronbach’s α 0.76-0.88). For regression, HBM constructs were aggregated into two composites (Health Perception, HPC; Prevention-Action, PAC). Two-block hierarchical linear regression modelled WSBRS on eight predictors. Results: Among 218 participants (mean age 67.8±6.4 years; 68.3% female), 42.7% had never undergone retinal examination. WSAS was moderate (3.42±0.58); WSBRS moderate (2.87±0.74). The full model explained 42.9% of variance (ΔR²=0.315; f²=0.751). WSAS (β=0.289), PAC (β=0.275), and HPC (β=0.215) were independently associated with WSBRS (all p≤0.001). Conclusions: Warning-sign awareness, prevention-oriented beliefs, and self-efficacy were independently associated with behavioural responses. Community nursing interventions targeting these constructs warrant prospective evaluation.